The combined effects of swimming exercise and stem cell transplantation on the expression of CD9 and CD63 tetraspanin genes in a rat model of azoospermia - Maziyar Shojaee; lida moradi; Parvin Farzanei; Bahram Abedi (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Azoospermia, defined as the absence of sperm in semen, is a common cause of male infertility. This study aimed to determine the combined effects of swimming exercise and stem cell transplantation on the expression of CD9 and CD63 tetraspanin genes associated with spermatogenesis in an animal model of azoospermia. Methods: In this experimental study, male rats were randomly divided into several groups after the induction of azoospermia. The groups included a healthy control group, an azoospermia group, an azoospermia + exercise group, an azoospermia + stem cell group, and an azoospermia + stem cell + exercise group. One million stem cells were transplanted into the vas deferens of each rat one month after the induction of azoospermia. Swimming exercise was performed daily for 30 minutes, 5 days a week for 8 weeks. After stem cell transplantation and exercise, the expression of CD9 and CD63 genes in testicular tissue was measured using Real-time PCR. Results: Both swimming exercise and stem cell transplantation, individually and in combination, had a significant effect on the expression of CD9 (F=23.475, P=0.001) and CD63 genes (F=19.186, P=0.002). These findings indicate that both interventions are effective in improving the spermatogenesis process in the animal model of azoospermia. Conclusion: The results of this study show that the combination of swimming exercise and stem cell transplantation can be considered as a novel therapeutic approach to improve fertility in men with azoospermia. The possible mechanism of this effect may be through the regulation of genes involved in spermatogenesis.